Method for manufacturing heat dissipation substrate and method for manufacturing composite substrate
Pulsed current sintering and re-pulse current sintering methods enhance thermal conductivity in diamond-metal composite materials, addressing the conductivity loss due to thinning processes.
Patent Information
- Application Number
- JP2021009002
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-10
- Filing Date
- 2021-01-22
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2041-01-22
AI Technical Summary
The thermal conductivity of composite materials containing diamond and metal, such as Cu-diamond MMC, is reduced during thinning processes, leading to decreased performance in heat dissipation applications.
A method involving pulsed current sintering with controlled pressure and temperature is applied to a composite material containing diamond and metal, followed by a thinning process and re-pulse current sintering to recover thermal conductivity.
The method significantly increases thermal conductivity, reducing the negative effects of thinning processes by repairing gaps and improving adhesion between diamond and metal interfaces.
Smart Images

Figure 0007602118000006 
Figure 0007602118000007 
Figure 0007602118000008
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for making a heat dissipation substrate containing diamond particles and a metal, and a method for making a composite substrate. [Background technology]
[0002] As the optical output of semiconductor light-emitting elements increases, heat dissipation from the semiconductor elements has become an important issue. Heat dissipation from semiconductor elements is an important issue not only for semiconductor light-emitting elements, but also for semiconductor integrated circuit elements that perform high-speed arithmetic processing, monolithic microwave integrated circuit elements that oscillate microwaves, and the like.
[0003] In order to dissipate heat from semiconductor elements that generate heat during operation, the development of heat dissipation components such as heat dissipation substrates that dissipate the heat from semiconductor elements is underway. Heat dissipation components are required to have high thermal conductivity. As a promising material for heat dissipation substrates, composite materials containing diamond and metals are being developed. This composite material has a structure in which diamond particles, which have a higher thermal conductivity than metals, are dispersed in metals such as copper (Cu).
[0004] Patent Document 1 discloses an example of a composite material in which diamond particles are dispersed in Cu. Patent Document 2 discloses a method of producing a composite material by coating diamond particles with a metal layer and then sintering them with Cu powder. Patent Document 3 discloses a heat dissipation substrate in which a plated metal layer is formed on a composite material in which diamond particles are dispersed in Cu. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2019-502251 [Patent Document 2] JP 2008-248324 A [Patent Document 3] International Publication No. 2016 / 056637 Summary of the Invention [Problem to be solved by the invention]
[0006] The present disclosure provides a method for manufacturing a heat dissipation substrate and a method for manufacturing a composite substrate that are capable of increasing the thermal conductivity that is reduced by a thinning process during the manufacturing process. [Means for solving the problem]
[0007] In one embodiment, the method for manufacturing a heat dissipation substrate of the present disclosure includes the steps of preparing a composite material containing diamond and a metal, thinning the surface of the composite material to form a processed surface on the composite material, and heating the composite material by pulse current sintering while applying a pressure of less than 50 MPa to the composite material.
[0008] In one aspect, a method for producing a composite substrate according to the present disclosure includes the steps of preparing a composite material containing diamond and a metal that has been subjected to a thinning treatment, and heating the composite material by pulse current sintering while applying a pressure of less than 50 MPa to the composite material. Effect of the Invention
[0009] According to the embodiment of the present disclosure, it is possible to increase the thermal conductivity, which is reduced by the thinning process during the manufacturing process, by pulse current sintering. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a graph plotting the linear expansion coefficient and thermal conductivity for materials such as diamond and Cu. [Diagram 2] FIG. 2 is a perspective view showing a schematic diagram of an example of a diamond particle 10. As shown in FIG. [Figure 3A] FIG. 3A is a flow chart illustrating major steps in a method for manufacturing a heat dissipation substrate according to an embodiment of the present disclosure. [Figure 3B]FIG. 3B is a flow chart showing the main steps in a method for producing a Cu-diamond composite material in accordance with an embodiment of the present disclosure. [Figure 4] FIG. 4 is a photograph showing an example of diamond particles contained in the mixed powder in an embodiment of the present disclosure. [Diagram 5] FIG. 5 is a schematic diagram showing an example of the configuration of a sintering device used in the pulse current sintering method according to the embodiment of the present disclosure. [Figure 6] FIG. 6 is a diagram showing a schematic example of the relationship between the time lapse from the start to the end of the pulse current sintering process and the temperature and pressure of the mixed powder. [Figure 7A] FIG. 7A is a diagram showing another example of the relationship between the time elapsed from the start to the end of the pulse current sintering process and the temperature and pressure of the mixed powder. [Figure 7B] FIG. 7B is a diagram showing another example of the relationship between the time elapsed from the start to the end of the pulse current sintering process and the temperature and pressure of the mixed powder. [Figure 8] FIG. 8 is a perspective view that illustrates a schematic external view of a composite material produced according to an embodiment of the present disclosure. [Figure 9] FIG. 9 is an enlarged schematic cross-sectional view of a portion of a composite material produced according to an embodiment of the present disclosure. [Figure 10] FIG. 10 is an enlarged cross-sectional view that illustrates a schematic view of a portion of a composite material that has been subjected to a thinning treatment in an embodiment of the present disclosure. [Figure 11] FIG. 11 is an enlarged cross-sectional view that illustrates a schematic diagram of a portion of a composite material that has been subjected to a wall-thinning treatment and a pulse current sintering treatment in sequence in an embodiment of the present disclosure. [Figure 12] FIG. 12 is an enlarged cross-sectional view that illustrates a schematic view of a portion of a composite material on which a metal layer is formed in an embodiment of the present disclosure. [Figure 13] FIG. 13 is a micrograph of a cross section of a part of the composite material in the experimental example. [Figure 14] FIG. 14 is a micrograph of a cross section of a part of a composite material in another experimental example. [Figure 15] FIG. 15 is a perspective view showing an application example of a composite material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Before describing the embodiments of the present disclosure, the findings of the present inventors and the technical background thereof will be described.
[0012] Figure 1 is a graph plotting the linear expansion coefficient and thermal conductivity of materials such as diamond and Cu. The horizontal axis of the graph is the linear expansion coefficient, and the vertical axis is the thermal conductivity. The linear expansion coefficient is the linear expansion rate per unit length, and its unit is [10 -6 / K]. The unit of thermal conductivity is [W / mK (Watts per meter per Kelvin)].
[0013] Single crystal diamond has the highest level of thermal conductivity among all substances, ideally exceeding 2000 [W / mK]. The thermal conductivity of polycrystalline diamond particles is, for example, about 900 to 1800 [W / mK]. The thermal conductivity of diamond particles produced by CVD method is, for example, about 900 to 1800 [W / mK].
[0014] FIG. 2 is a perspective view showing a schematic example of a diamond particle 10. The diamond particle 10 in the example of FIG. 2 has a polyhedral shape with, for example, hexagonal and quadrangular faces (facets) on the surface. In actual diamond particles, other polygonal faces may appear on the surface or some may be missing, and the particles may have more complex and diverse shapes. The thermal conductivity of each diamond particle may have different values depending on the presence of crystal defects or impurities present on the surface or inside.
[0015] On the other hand, the thermal conductivity of the metal Cu is about 400 [W / mK], and that of Ag is about 420 [W / mK]. Therefore, the thermal conductivity of a composite material in which diamond particles are dispersed in a metal such as Cu is intermediate between the thermal conductivity of the metal and that of the diamond particles. The higher the volume ratio of diamond particles in the composite material, the higher the theoretical value of the thermal conductivity of the composite material. However, in reality, the thermal conductivity of a composite material is not simply determined by the volume ratio of diamond alone, and it is thought that the state of the interface between Cu and diamond particles also affects it. The interface between Cu and diamond can fluctuate due to defects and damage that may occur in the diamond particles during the manufacturing process.
[0016] When a semiconductor element is bonded to a heat dissipation substrate for use, if there is a large difference in the linear expansion coefficient between the member in contact with the heat dissipation substrate on the semiconductor element side and the heat dissipation substrate, problems such as peeling may occur. For this reason, it is desirable for the linear expansion coefficient of the composite material used in the heat dissipation substrate to be close to the linear expansion coefficient of the member to be bonded.
[0017] Composite materials containing diamond particles and Cu have excellent properties, such as a higher thermal conductivity than Cu and a linear expansion coefficient close to that of semiconductors. Composite materials with a metal matrix are sometimes called metal matrix composites (MMCs). For this reason, composite materials with diamond particles dispersed in Cu are sometimes referred to as "Cu-diamond MMCs" in this specification. They may also be simply referred to as "Cu-diamond composite materials" or "composite materials." The metal that serves as the matrix for MMCs is not limited to Cu, but can also be Ag, Al, etc.
[0018] When bonding a heat dissipation substrate to a semiconductor element, it is preferable that the thickness can be adjusted as necessary. However, when the inventor performed polishing on a Cu-diamond MMC, the thermal conductivity of the polished Cu-diamond MMC was lower than that of the Cu-diamond MMC before polishing. It is believed that the polishing process reduces the adhesion between diamond and Cu in the Cu-diamond MMC, which is why the thermal conductivity is reduced.
[0019] The inventors have also found that the thermal conductivity, which had decreased after the polishing process, can be increased by performing low-temperature, low-pressure pulse current sintering after the polishing process to damage the Cu-diamond composite material produced in this way. In the polishing process, the surface of the Cu-diamond composite material is scraped off. As a result, the entire or part of the diamond particles present near the surface of the composite material are scraped off or dropped off from the composite material together with the surrounding Cu. The removal of diamond particles from the Cu-diamond composite material by polishing is called "grain shedding." When such grain shedding occurs, the smoothness of the surface of the Cu-diamond composite material is impaired. Thus, the processed surface formed on the surface of the composite material by the polishing process, that is, the polished surface, is not smooth, and unevenness having the same size as the diamond particles may exist on the processed surface. In addition, such a polishing process may cause gaps to occur at the interface between the Cu and the diamond particles due to the stress applied during polishing to the diamond particles remaining in the composite material. As a result, the thermal conductivity of the composite material after the polishing process is lower than that of the composite material before the polishing process. However, it was found that when the composite material after polishing is subjected to pulsed current sintering, which will be described later, the thermal conductivity increases. This is thought to be due to the fact that the gaps between the diamond particles and the Cu interface are repaired. Hereinafter, this type of pulsed current sintering performed after the polishing process may be referred to as "re-pulsed current sintering" to distinguish it from pulsed current sintering, which is an example of a method for producing composite materials.
[0020] The method for manufacturing a heat dissipation substrate according to the present disclosure has been completed based on the above-mentioned new findings. Hereinafter, an embodiment of the method for manufacturing a heat dissipation substrate according to the present disclosure will be described. Note that the heat dissipation substrate is an example of the composite substrate according to the present disclosure.
[0021] <Embodiment> 3A is a flow chart showing the main steps of the method for manufacturing a heat dissipation substrate according to an embodiment of the present disclosure. As shown in FIG. 3A, the method for manufacturing a heat dissipation substrate in this embodiment includes a step S100 of preparing a composite material containing diamond and copper, a step S200 of thinning the surface of the composite material to form a processed surface on the composite material, and a step S300 of heating the composite material by pulse current sintering while applying a pressure of less than 50 MPa to the composite material.
[0022] Below, we will explain the case where the metal used in the composite material is Cu. Note that, as metals other than Cu, for example, Al and silver (Ag) can be used. The thermal conductivity of the metal is preferably 200 [W / mK] or more. Since the thermal conductivity of Al is about 240 [W / mK] and that of Ag is about 420 [W / mK], high thermal conductivity can be maintained even when a composite material is formed with diamond.
[0023] First, the step S100 of preparing a composite material in this embodiment will be described. FIG. 3B is a flow chart showing a specific example of the step S100 of preparing a composite material according to this embodiment. As described above, the cause of the decrease in thermal conductivity of the composite material is considered to be due to the polishing process. Therefore, the effect of the embodiment of the present disclosure does not depend on the manufacturing method of the composite material to be prepared. That is, in this embodiment, various composite materials manufactured by known methods can be used, and for example, commercially available composite materials may be used. Examples of methods for manufacturing a composite material include a sintering method and a melting method. A preferred method for manufacturing a composite material is a pulse current sintering method. With this method, a composite material can be obtained under relatively low temperature conditions compared to the conventional method, as described later.
[0024] Hereinafter, a method for manufacturing a composite material by the pulse current sintering method will be described with reference to FIG. 3B. As shown in FIG. 3B, this step S100 includes a step S10 of preparing a mixed powder of diamond particles and Cu powder particles, and a step S20 of producing a composite material containing diamond and Cu from the mixed powder by applying pressure to the mixed powder and holding it at a temperature of 500°C or more and less than 800°C by the pulse current sintering method. This "temperature" is a "temperature" measured directly or indirectly by a temperature measuring device such as a radiation thermometer or a thermocouple. The "temperature" in this disclosure is a measured value of the temperature in the die 30 of the SPS device as shown in FIG. 5 described later. Note that the sintering peak temperature Ts described later means a temperature that is held at a predetermined pressure for a total of 1 minute or more among the temperatures of the die 30 measured by a radiation thermometer or a thermocouple. For example, in the case of FIG. 6, the temperature held at the highest temperature in the sintering process is called the sintering peak temperature Ts, and is distinguished from the temperature that changes transiently during the temperature rise and fall.
[0025] FIG. 4 is a photograph showing an example of diamond particles contained in the mixed powder of step S10. In one embodiment, the average particle size of the diamond particles is 40 μm or more and 500 μm or less. The particle size distribution of the diamond particles does not need to be a single peak, and may have multiple peaks. By making the average particle size of the diamond particles 40 μm or more, the thermal conductivity can be increased while manufacturing the Cu-diamond MMC at low cost. By making the average particle size of the diamond particles 500 μm or less, the manufacturing cost of the diamond particles themselves can be reduced. In addition, the particle size distribution of the diamond particles is preferably 200 μm or more and 400 μm or less. Within this range, the thermal conductivity can be further improved. In one embodiment, the diamond particles in the mixed powder may include particles with an average particle size of 200 μm or more and 400 μm or less and particles with an average particle size of 40 μm or more and 80 μm or less. In this specification, particles with an average particle size of 200 μm to 400 μm are called "large particles," and particles with an average particle size of 40 μm to 80 μm are called "small particles." Particles with a relatively small average particle size can be arranged to fill the gaps between particles with a relatively large average particle size, so that the amount of diamond, which has a higher thermal conductivity than Cu, can be increased. This can further improve the thermal conductivity of the Cu-diamond MMC. A mixed powder with such a bimodal particle size distribution is called a "bimodal mixed powder" in this specification. In a bimodal mixed powder, the ratio of particles with an average particle size of 200 μm to 400 μm to the total diamond particles is preferably 50% or more by mass. This is because the more particles with a larger average particle size there are, the smaller the total surface area of the diamond particles becomes, and the smaller the contribution of the thermal resistance at the interface between the diamond particles and Cu becomes.
[0026] The average particle size of the Cu powder particles is, for example, 3 μm or more and 10 μm or less. The Cu powder may contain Cu fine powder having a particle size of 1 μm or less that may be generated by pulverization or the like. The Cu powder particles may contain unavoidable impurities. However, since impurities such as oxygen and nitrogen cause a decrease in thermal conductivity, it is desirable to remove them as much as possible. The content of impurities in the Cu powder particles is preferably 2 mass% or less. Such Cu powder particles may be manufactured by a known manufacturing method. Also, commercially available Cu powder particles may be used.
[0027] In addition, the "average particle size" in this disclosure means the "median diameter" in the particle size distribution measured by a laser diffraction particle size distribution measuring device.
[0028] In the embodiment of the present disclosure, no metal other than Cu powder particles is intentionally added to improve wettability. Conventionally, it has been thought that it is necessary to improve wettability by adding metal because Cu and diamond have poor wettability, but in the embodiment of the present disclosure, such an added metal is not necessary. By not intentionally adding metal other than Cu powder particles, sintering inhibition can be reduced. In one embodiment, the amount of metal other than Cu added to the mixed powder is 1% or less by mass ratio.
[0029] In addition, as described above, in order to improve the adhesion between diamond particles and Cu powder particles, each diamond particle may be coated with a metal layer such as copper, but in the embodiment of the present disclosure, diamond particles are not coated with a metal layer.This is because by not coating diamond particles with a metal layer such as Cu in advance, sintering activity can be increased compared to the case where diamond particles are coated with a metal layer such as Cu in advance.If diamond particles are coated with a metal layer such as Cu in advance, sintering activity decreases, and sintering at high temperature is required as in the case where metal is added.
[0030] In this embodiment, the mass ratio of Cu powder particles in the mixed powder is preferably, for example, 60% or more and 85% or less, and the mass ratio of diamond particles in the mixed powder is preferably, for example, 15% or more and 40% or less. In other words, the mass ratio of Cu powder particles to diamond particles is selected within the range of 60:40 to 85:15, for example, 80:20. The thermal conductivity of the composite material increases as the mass ratio of diamond particles increases. By setting the mass ratio of Cu powder particles to 60% or more and 85% or less, a sufficient amount of copper is arranged around the diamond, and gaps that inhibit heat conduction are less likely to occur in the Cu-diamond MMC. In other words, if the mass ratio of Cu powder particles is within the above range, Cu can have a volume sufficient to be arranged around the diamond, so that the gaps between the diamond particles are easily filled effectively. In addition, if the amount of Cu is too large, the thermal conductivity of Cu is lower than that of diamond, so the thermal conductivity of Cu-diamond MMC may decrease, but within the above range, a Cu-diamond MMC with high thermal conductivity can be manufactured. Also, as described later, according to the inventor's experiment, even if the mass ratio of diamond particles is the same, bimodal mixed powder is more likely to achieve high thermal conductivity.
[0031] The pulse current sintering method in step S20 can be performed using a sintering apparatus 100 as shown in FIG. 5, for example. The pulse current sintering method is sometimes called a spark plasma sintering method (SPS). For this reason, the sintering apparatus 100 in FIG. 5 may be called an "SPS apparatus." The sintering apparatus 100 in FIG. 5 includes a die 30 having a through hole that forms a cavity 20, and an upper punch 40 and a lower punch 50 that can move relatively up and down along the through hole of the die 30. The sintering apparatus 100 in this example can perform sintering using self-heating under vertical uniaxial pressure. The upper punch 40 is electrically connected to a first electrode 51, and the lower punch 50 is electrically connected to a second electrode 52. The first electrode 51 and the second electrode 52 are electrically connected to a power supply unit 60.
[0032] The die 30 may be made of a material having excellent heat resistance, such as graphite. The upper punch 40 and the lower punch 50 may be made of a material having electrical conductivity and heat resistance, such as graphite. In the thermal conductivity measurement, the flatter the sample, the more reliable the thermal diffusivity can be measured. Therefore, when it is difficult to ensure the flatness of the sintered body to be manufactured, it is preferable to insert a hard material between the upper punch 40 and the sample and between the lower punch 50 and the sample to obtain a sintered body having a flat surface. The hard material is preferably a cemented carbide, such as tungsten carbide (WC) or titanium carbide (TiC). The material of the upper punch 40 and the lower punch 50 may be changed to the material. The cavity 20 is a space defined by the inner wall surface of the through hole of the die 30, the lower end surface of the upper punch 40, and the upper end surface of the lower punch 50. The above-mentioned mixed powder is loaded into the cavity 20. By moving at least one of the upper punch 40 and the lower punch 50 in the vertical direction, the distance between the upper punch 40 and the lower punch 50 decreases, and pressure is applied to the mixed powder in the cavity 20. The upper punch 40 and the lower punch 50 are driven, for example, by a hydraulic device (not shown). The pressure applied to the mixed powder in the cavity 20 can be adjusted arbitrarily, for example, within the range of 5 MPa to 100 MPa.
[0033] In the pulse current sintering method, a pulse current is applied between the upper punch 40 and the lower punch 50 while applying pressure to the mixed powder by the sintering device 100. The pulse current is applied by repeatedly passing a direct current pulse current from the power supply unit 60 between the first electrode 51 and the second electrode 52. In the mixed powder pressurized by the upper punch 40 and the lower punch 50, the Cu powder particles are in contact with each other, so that a number of local current paths are formed in the mixed powder, through which a current flows. This pulse current generates Joule heat, and the temperature of the mixed powder rises to a predetermined sintering temperature.
[0034] FIG. 6 is a diagram showing an example of how the temperature and pressure of the mixed powder change with time from the start to the end of the pulse current sintering process. The temperature is shown by a dashed line, and the pressure is shown by a solid line. The horizontal axis indicates time, the left vertical axis indicates temperature, and the right vertical axis indicates pressure. By moving the upper punch 40 and / or the lower punch 50, the pressure reaches the sintering pressure Ps in, for example, several seconds, and the sintering pressure Ps is maintained for, for example, 60 to 1800 seconds. By starting the pulse current, the temperature of the mixed powder increases at a rate of, for example, 10 to 150 [°C / min] or more. After reaching a predetermined sintering peak temperature Ts, the sintering peak temperature Ts is maintained within ±5°C of the target temperature by adjusting the voltage application conditions of the pulse current. The sintering temperature can be controlled by feedback of measurements by a temperature measuring device attached to the die 30 in FIG. 5.
[0035] After a predetermined sintering time has elapsed and a composite material has been produced from the mixed powder, the pulse current is stopped and the temperature is lowered. The upper punch 40 and / or the lower punch 50 are moved to stop applying pressure to the composite material. After the temperature of the composite material has sufficiently decreased to, for example, 50° C. or lower, the composite material is removed from the die 30.
[0036] In Figure 6, the temperature and pressure are shown to increase and remain linearly over time for ease of illustration, but in reality the temperature and pressure progression may include slight overshoots, curvilinear changes, small oscillations, etc.
[0037] In this embodiment, the voltage when maintaining the sintering temperature is adjusted in the range of 1.0 V or more and 3.0 V or less, and the pulse current is adjusted in the range of 400 A or more and 800 A or less. The duty ratio of the pulse current is, for example, 10 to 80%, and the pulse width is, for example, 1 to 500 milliseconds. After holding at a predetermined sintering peak temperature Ts for a predetermined time, the pulse current is stopped. Note that these values vary depending on various conditions such as the weight of the mixed powder, the sintering temperature, and the material of the punch, and are not limited to the above ranges and can be changed as appropriate.
[0038] When the sintering temperature is set to, for example, 600°C, the time required to reach the sintering temperature from room temperature is, for example, several minutes to about 20 minutes. The cavity 20 is located in a decompression chamber (not shown). The atmospheric pressure in the decompression chamber is, for example, 100 Pa or less. In this way, the powder particles can be prevented from being oxidized or nitridized during the sintering process by pulse current application.
[0039] As described above, the sintering peak temperature Ts in the embodiment according to the present disclosure is 500°C or more and less than 800°C. In this range, a Cu-diamond MMC having excellent thermal conductivity can be manufactured. In addition, a preferred sintering peak temperature Ts is 500°C or more and 750°C or less. More preferably, it is 550°C or more and 700°C or less. Particularly preferably, it is 600°C or more and 700°C or less. In the above range, a Cu-diamond MMC having even better thermal conductivity can be obtained. The range of the sintering time also depends on the sintering peak temperature Ts, and is, for example, in the range of 1 minute or more and 30 minutes or less. When the sintering peak temperature Ts is, for example, 550°C or more and 650°C or less, the sintering time can be 5 minutes or more and 20 minutes or less, for example, about 10 minutes.
[0040] The pressure applied to the mixed powder at the above sintering peak temperature Ts is 5 MPa or more and 100 MPa or less when held at a constant pressure. By applying a pressure of 5 MPa or more and 100 MPa or less, a Cu-diamond MMC having excellent thermal conductivity can be manufactured. A preferable pressure range is 10 MPa or more and 90 MPa or less. A more preferable pressure range is 20 MPa or more and 90 MPa or less. Even more preferable is 25 MPa or more and 75 MPa or less. Particularly preferable is 25 MPa or more and 50 MPa or less. Within these pressure ranges, a Cu-diamond MMC having excellent thermal conductivity can be manufactured. As described above, applying a constant pressure at the sintering peak temperature Ts is referred to as "continuous pressurization" in this specification.
[0041] Although the above description concerns the case of continuous pressurization, the pressure does not have to be constant. The applied pressure may be increased or decreased stepwise or continuously according to the progress of sintering. In addition, a first pressure and a second pressure higher than the first pressure may be repeatedly applied to the mixed powder while applying a pulse current. This type of pressurization is called "cyclic pressurization." In the above cyclic pressurization, a Cu-diamond MMC with high thermal conductivity can be manufactured by repeatedly applying a first pressure and a second pressure higher than the first pressure. This is believed to be due to the mechanism described below, for example.
[0042] There is a difference in absolute value between the first pressure and the second pressure. When these pressures are repeatedly applied, there is a step of applying the first pressure after applying the second pressure. At this time, since a relatively high pressure is applied followed by a relatively low pressure, the diamond particles have more freedom in the die when the first pressure is applied compared to when the second pressure is applied. This is thought to make the arrangement of the diamond particles or the state of the interface between the Cu and the diamond particles more favorable for heat conduction. It is also possible that oxygen that is present on the Cu surface and inhibits heat conduction is removed. As a result, it is thought that the Cu-diamond MMC produced by the cyclic pressurization has improved thermal diffusivity and higher thermal conductivity compared to when only the first pressure is applied.
[0043] The pressures applied to the mixture of diamond particles and Cu powder particles can be set as a first pressure and a second pressure in the range of 5 MPa to 100 MPa, respectively, under the condition that the second pressure is greater than the first pressure. The first pressure may be 5 MPa to 60 MPa, and the second pressure may be 20 MPa to 100 MPa. Preferably, the first pressure is 5 MPa to less than 20 MPa, and the second pressure is 20 MPa to 40 MPa. By setting the first pressure and the second pressure in the above ranges, respectively, the thermal conductivity can be further improved.
[0044] FIG. 7A is a diagram showing an example of "cyclic pressure application" during sintering. In this example, a first pressure P1 and a second pressure P2 higher than the first pressure P1 are repeatedly applied to the mixed powder during the sintering time. As an example, when the first pressure P1 is 10 MPa and the second pressure P2 is 40 MPa, the operation of applying the first pressure P1 for 10 seconds and then applying the second pressure P2 for 20 seconds is regarded as one cycle, and for example, 10 to 50 cycles of pressure application can be repeated during the sintering process. As will be described later, by varying the pressure during the sintering time, the obtained composite material is densified and the relative density is increased. This contributes to increasing the thermal conductivity of the composite material.
[0045] Fig. 7B is a diagram showing another example of "cyclic pressure" during sintering. As shown in Fig. 7B, a first pressure and a second pressure higher than the first pressure may be repeatedly applied to the mixed powder from the temperature rise stage. In addition, the first pressure and the second pressure may be repeatedly applied during the holding time of the sintering peak temperature Ts.
[0046] FIG. 8 is a perspective view showing a schematic example of the outer shape of the composite material 80 produced by the present embodiment. In this example, the composite material 80 has a disk shape with a thickness T [mm] and a radius R [mm]. The thickness T is, for example, 0.2 mm or more and 20.0 mm or less. The radius R is, for example, 3 mm or more and 200 mm or less. The shape of the composite material 80 immediately after sintering is not limited to a disk shape, and may have a rectangular parallelepiped or other polyhedral shape, or may have a shape with striped grooves or a regular uneven pattern on the surface. The shape of the composite material 80 in a top view immediately after sintering is determined by the shape of an axial cross section perpendicular to the cavity 20 in FIG. 5. For example, when the die 30 in FIG. 5 has a prismatic through hole, and the lower end surface of the upper punch 40 and the upper end surface of the lower punch 50 are flat rectangular surfaces, the composite material 80 taken out of the sintering apparatus 100 may have a thin plate shape that is rectangular in top view. After being removed from the sintering apparatus 100, the composite material 80 is thinned to obtain a desired thickness. The thinning process includes cutting, polishing such as grinding, and laser processing. It is also possible to separate a plurality of heat dissipation members from one composite material 80.
[0047] FIG. 9 is a schematic diagram showing an enlarged part of the cross section of the composite material 80 thus produced. FIG. 9 is based on cross-sectional observation by an optical microscope. The composite material 80 shown in FIG. 9 contains Cu70, which is a metal matrix, and a large number of diamond particles 10 dispersed in Cu70. Cu70 is a metal body in which Cu powder particles contained in the mixed powder are sintered and integrated by pulse current. Each diamond particle 10 contained in the composite material 80 is a diamond particle contained in the mixed powder. Although some of the diamond particles 10 may be chipped during the pulse current sintering process, multiple diamond particles do not bond together to grow into a new particle.
[0048] According to the above-mentioned method for producing a composite material, by producing a Cu-diamond composite material at a lower temperature and pressure than those of the prior arts 1 and 2, the thermal conductivity of the composite material can be, for example, 460 [W / mK] or more. Also, a composite material having a thermal conductivity of 500 [W / mK] or more can be obtained. Furthermore, it is possible to make it 600 [W / mK], preferably 690 to 710 [W / mK] or more. This is considered to be because the deterioration of thermal conductivity at the diamond particles or Cu / diamond interface that occurs during high-temperature and high-pressure sintering can be suppressed or avoided by lowering the sintering temperature and pressure lower than those previously considered necessary.
[0049] According to the above-mentioned manufacturing method for the composite material, the temperature difference until the Cu-diamond MMC is cooled to room temperature after pulse current sintering is smaller than that in Prior Arts 1 and 2. In the first embodiment, the amount of expansion and contraction of copper and diamond depending on the difference in linear expansion coefficient is smaller than that in Prior Arts 1 and 2. That is, since copper and diamond are less likely to peel off due to the difference in linear expansion coefficient, the decrease in thermal conductivity can be reduced.
[0050] Referring again to FIG. 3A, step S200 will be described. In step S200, the Cu-diamond composite material is thinned. The thinning process includes polishing and laser processing. The polishing process can be performed by various polishing methods such as rough polishing, fine polishing, fixed abrasive method (grinding), and loose abrasive method (polishing).
[0051] In this disclosure, "polishing" includes "grinding" which scrapes off the surface of the composite material 80 with abrasive grains having high hardness such as diamond. In general, "grinding" means scraping off the surface of the workpiece to be processed with abrasive grains, and the surface that appears by grinding, i.e., the processed surface, is not necessarily smooth. On the other hand, "polishing" means scraping off the surface of the workpiece to be processed with abrasive grains and forming a smooth surface. Since the Cu-diamond composite material contains diamond, an ideally smooth surface may not be formed even if polishing is performed. Diamond particles are removed from the surface of the composite material due to collision or friction with the abrasive grains, so that even after polishing, unevenness of about the size of the diamond particles may remain on the processed surface of the composite material. For this reason, in this disclosure, polishing and grinding are not distinguished, and the "polishing process" is broadly defined as the process of polishing and / or grinding.
[0052] FIG. 10 is a cross-sectional view showing the vicinity of the processed surface 80P of the composite material 80. The portion cut off by the thinning process is denoted by the reference symbol "80X". In the example of FIG. 10, the processed surface 80P has irregularities of about the size of the diamond particles 10. The thickness of the composite material 80 depends on the size of the package in which the composite material is mounted. Therefore, the thinning process is performed until the composite material has a desired thickness. For example, when the thickness of the composite material 80 before the thinning process is 1 mm, the thickness of the composite material 80 after the thinning process can be 100 μm or more and 800 μm or less. Such a polishing process makes it possible to make the thickness of the composite material 80 immediately after the pulse current sintering sufficiently larger than the thickness of the heat dissipation member required in the end. According to the inventor's experiments, it was found that if the composite material 80 to be produced is too thin, the distribution of heat generated by the pulse current sintering during the sintering process becomes non-uniform, and the characteristic variation of the composite material 80 increases. Therefore, on the premise that the thickness is adjusted to a target value by the thinning process, if the composite material 80 is formed to be thicker than the target value, it becomes possible to suppress or reduce the variation in characteristics.
[0053] However, further study by the present inventors has revealed that the thermal conductivity of the composite material 80 after the thinning process may decrease to, for example, about 80% of the thermal conductivity before the polishing process. This is due to the decrease in the relative density and thermal diffusivity of the composite material 80. The reason for this is thought to be that, for example, when polishing is performed, when a part of the composite material 80 is scraped off, stress is generated, and the thermal resistance at the interface between the diamond particles 10 and Cu70 increases. In addition, it is thought that one of the causes is that the adhesion between the diamond and Cu inside the composite material decreases due to vibration during polishing. The decrease in relative density means that multiple voids are generated inside the composite material 80. In addition, when laser processing is performed, heat is applied locally to the composite material, and the temperature of the composite material increases. As a result, the adhesion between the diamond particles 10 and Cu70 inside the composite material may decrease due to the difference in linear expansion coefficient. Hereinafter, the cause of the decrease in thermal conductivity that may occur due to such thinning processing will be referred to as the "defect" or "damage" of the composite material. The decrease in thermal conductivity caused by the thinning process as described above can occur even when the matrix of the composite material is a metal other than Cu.
[0054] In this embodiment, as shown in FIG. 3A, after the step S200 of performing the thinning process, the step S300 of defect recovery by re-pulse current sintering is performed. In this step S300, it is possible to alleviate the degree of defects or damage caused by the thinning process or to restore the original state. As a result, it is possible to increase the thermal conductivity decreased by the thinning process. In other words, the re-pulse current sintering can increase the thermal diffusivity of the composite material 80 to be higher than the thermal diffusivity before the re-pulse current sintering. The re-pulse current sintering can be performed in a state where a pressure of less than 50 MPa is applied to the composite material. By performing the re-pulse current sintering at a pressure of less than 50 MPa, the composite material is sintered again densely, so that the thermal conductivity decreased by the thinning process can be effectively improved.
[0055] In one embodiment, the re-pulse current sintering is performed under low temperature and low pressure conditions. Specifically, in a sintering apparatus 100 as shown in FIG. 5, the composite material 80 after the thinning process is loaded into the cavity 20 formed between the upper punch 40 and the lower punch 50. As the sintering apparatus 100, a sintering apparatus capable of performing pulse current sintering is used. When the composite material 80 is obtained by pulse current sintering a mixed powder of Cu and diamond, a sintering apparatus that is the same as or of the same type as that used when the composite material 80 was produced may be suitably used. By the re-pulse current sintering, the composite material 80 is held at a temperature of, for example, 500°C or higher and lower than 800°C while applying a pressure of, for example, 5 MPa or higher and 50 MPa or lower. The pressure applied is preferably 5 MPa or higher and 40 MPa or lower. The holding time depends on the holding temperature, but is, for example, 60 seconds or higher and 1800 seconds or lower. The pressure may be applied by the above-mentioned "cycle pressurization". The pulse current sintering method for increasing the thermal conductivity decreased by the thinning treatment may include continuous pressing and cyclic pressing under the above conditions, for example, as described with reference to FIGS. 6 and 7A and 7B.
[0056] 11 is a cross-sectional view showing the state of the composite material 80 after the thinning process and re-pulse current sintering. As a result of the re-pulse current sintering, the degree of defects or damage caused by the thinning process is alleviated, and the original state can be restored. This is thought to be because the relative density of the composite material 80 increases under the temperature and pressure in the re-pulse current sintering process, the thermal resistance at the interface between the diamond particles and Cu decreases, and the heat dissipation path is shortened, increasing the thermal diffusivity.
[0057] It was also found that the thermal diffusivity of the composite material becomes higher after the re-pulse current sintering than before the re-pulse current sintering. Here, the thermal conductivity and thermal diffusivity have the following relationship: Thermal conductivity [W / m K] = Thermal diffusivity [m 2 / s] × specific heat [J / K kg] × density [kg / m 3 ]
[0058] According to the results of an experiment described later, both the relative density and thermal conductivity, which were decreased by the thinning treatment, are increased by the re-pulse current sintering. Also, according to Example 1 described later, for example, the rate at which the thermal conductivity increases is greater than the rate at which the relative density increases by the re-pulse current sintering. This means that the re-pulse current sintering increases the thermal diffusivity itself of the composite material 80, which was decreased by the thinning treatment. In other words, it is considered that the re-pulse current sintering not only increases the relative density of the composite material after the thinning treatment, but also contributes to repairing defects and damage caused by the thinning treatment.
[0059] The re-pulse current sintering may be performed with a metal powder or metal plate in contact with the processing surface 80P of the composite material 80. Examples of these metals include Cu, Al, CuW, and CuMo. From the viewpoint of thermal conductivity and ease of handling, it is preferable to use Cu. Also, from the viewpoint of reducing the difference in thermal expansion with the composite material 80, it is preferable to use CuW. The Cu powder or Cu plate is easily bonded and integrated with the Cu of the composite material 80. By the re-pulse current sintering, the metal powder can form a metal layer bonded to the processing surface 80P of the composite material 80. Also, the metal plate in contact with the processing surface 80P of the composite material 80 can form a metal layer bonded to the processing surface 80P of the composite material 80 by the re-pulse current sintering. If the "metal plate" is sufficiently thin, it is not necessary for it to have self-supporting rigidity. Such a thin metal plate may be called a thin metal film or foil.
[0060] 12 is a cross-sectional view showing a schematic diagram of a part of a composite material 80 having a metal layer 82 thus formed. The metal layer 82 formed by the re-pulse current sintering is sintered together with the underlying composite material 80. In particular, when the metal layer 82 is made of Cu, it is continuous with the Cu constituting the composite material 80. This sintering together makes it possible to bond the composite material 80 and the metal layer 82 more firmly than when a metal is bonded to the processed surface 80P of the composite material 80 by a physical or chemical method, or when a metal layer is bonded to the composite material 80 via a bonding material.
[0061] During the re-pulse current sintering process, the surface of the metal layer 82 is pressed against the lower end surface of the upper punch 40, for example, in a sintering apparatus 100 shown in Fig. 5. As described above, the pressure at this time is, for example, 5 MPa or more and 50 MPa or less, and the temperature is, for example, 500°C or more and less than 800°C. This allows the softened metal to bond strongly to the processing surface 80P. Moreover, the pressure at this time is preferably 5 MPa or more and 40 MPa or less.
[0062] Since the thermal conductivity of the metal layer 82 is at most about 400 [W / mK], if the metal layer 82 is too thick, the thermal conductivity of the heat dissipation substrate in which the composite material 80 and the metal layer 82 are integrally sintered decreases. For this reason, the thickness of the metal layer 82 is preferably, for example, 50 μm or more and 500 μm or more.
[0063] When metal layer 82 is formed by pulse current sintering with metal powder in contact with the processed surface of composite material 80, it is easy to increase the adhesion of metal layer 82 to composite material 80.
[0064] Furthermore, when the metal layer 82 is formed by performing re-pulse current sintering with a metal plate in contact with the processed surface of the composite material 80, a metal plate having a predetermined thickness can be used, which has the advantage that the thickness of the metal layer 82 can be easily made close to the target value. Furthermore, when a metal plate is used, the thermal conductivity of the metal plate can be maintained close to the thermal conductivity of the metal material. Therefore, by making the composite material 80 to have a predetermined thickness or more, it is easy to improve the thermal conductivity of the heat dissipation substrate in which the composite material 80 and the metal layer 82 are sintered together.
[0065] The metal layer 82 thus formed does not substantially contain diamond particles 10, and therefore can form a smoother surface than the processed surface 80P of the composite material 80. The smooth surface contributes to increasing the effective contact area and reducing the thermal resistance when a heat source such as a semiconductor light emitting element and a heat dissipation member are in thermal contact with each other. In addition, the metal layer 82 being located on the surface of the composite material 80 also has the effect of facilitating plating and the like.
[0066] The composite material 80 having the metal layer 82 thus obtained is diced into individual pieces, thereby making it possible to obtain a plurality of heat dissipation substrates from the composite material 80. Alternatively, the composite material 80 may be used as a single heat dissipation substrate without being diced into individual pieces.
[0067] Moreover, the re-pulse current sintering can be performed without contacting metal powder or a metal plate on the processed surface 80P of the composite material 80. In this case, a material with a lower thermal conductivity than diamond is not added to the composite material. Therefore, the thermal conductivity of the heat dissipation substrate after the re-pulse current sintering is improved, and can be made close to that of the original composite material.
[0068] <Example 1> First, a Cu-diamond MMC composite material was prepared. The composite material was obtained by the following method. Cu powder particles with an average particle size of 5 μm and diamond particles with an average particle size of 250 μm were mixed to obtain a mixed powder. The total weight of the mixed powder was 6.24 grams. With respect to the total mixed powder, the Cu powder particles were 60 mass percent, the diamond particles with an average particle size of 250 μm were 20 mass percent, and the diamond particles with an average particle size of 60 μm were 20 mass percent. Next, a Cu-diamond MMC with a thickness of 3 mm was produced using a sintering device manufactured by SPS Syntex (model number SPS-515S). The sintering peak temperature Ts was 670°C, and the applied pressure was 36 MPa. The holding time of the sintering peak temperature Ts was 10 minutes. The vacuum degree at the start of sintering was 10 Pa. The size of the composite material was 20 mm in diameter x 2.731 mm in thickness. After obtaining the composite material, the density and thermal diffusivity were measured. The preparation conditions for the above composite materials are shown in Table 1.
[0069] Next, the prepared composite material was polished to form a machined surface on the composite material. The thickness was reduced by 0.184 mm by this polishing process. After forming the machined surface, the density and thermal diffusivity were measured.
[0070] Next, the composite material with the processed surface was subjected to pulse current sintering using the above sintering device to obtain a heat dissipation substrate. This pulse current sintering was performed on the composite material alone, without contacting the processed surface of the composite material with Cu powder or Cu plate. The sintering peak temperature Ts was 660°C, and the applied pressure was 36 MPa. The retention time at the sintering peak temperature Ts was 10 minutes. The degree of vacuum at the start of sintering was 10 Pa. This pulse current sintering reduced the thickness of the composite material by 0.122 mm. After obtaining the heat dissipation substrate, the density and thermal diffusivity were measured.
[0071] In Example 1 and each of the examples described later, the current value while maintaining the sintering peak temperature Ts was in the range of 350 A to 700 A. The pulse width of the applied voltage was 3.3 milliseconds.
[0072] <Example 2> A heat dissipation substrate was obtained in the same manner as in Example 1, except for the following points.
[0073] In preparing the composite material, the mixing ratio of Cu powder particles and diamond particles was changed. The Cu powder particles were 65 mass percent of the total mixed powder, the diamond particles with an average particle size of 250 μm were 20 mass percent, and the diamond particles with an average particle size of 60 μm were 15 mass percent. Pulse current sintering was performed with a sintering peak temperature Ts of 660°C. The manufacturing conditions of the above composite material are shown in Table 1.
[0074] The composite material was polished to form a processed surface, and then a Cu plate was placed in contact with the processed surface and pulse current sintering was performed again to obtain a heat dissipation substrate. The conditions for pulse current sintering were the same as those for preparing the composite material.
[0075] <Example 3> A heat dissipation substrate was obtained in the same manner as in Example 2, except for the following points.
[0076] In preparing the composite material, the first pressure was set to 10 MPa, and the second pressure was set to 36 MPa, and these were repeatedly applied. The applied pressures were held for 15 seconds for the first pressure and 20 seconds for the second pressure, with a total pressure switching time of 50 seconds, for a total time of 85 seconds per cycle. The number of repeated cycles was 25. The holding time of the sintering peak temperature Ts was 20 minutes. The preparation conditions for the above composite material are shown in Table 1.
[0077] The composite material was polished to form a machined surface, and then pulse current sintering was performed with Cu powder particles in contact with the machined surface to obtain a heat dissipation substrate. The pulse current sintering conditions were the same as those for preparing the composite material.
[0078] [Table 1]
[0079] <Thermal conductivity> The thermal conductivity was determined for each of Examples 1 to 3. The thermal conductivity can be determined as the product of the specific heat, density, and thermal diffusivity. The specific heat was obtained by weighting the literature values of the specific heat of diamond and Cu by the mixed mass ratio. The density was measured by the Archimedes method. The thermal diffusivity was obtained by a flash method using a xenon lamp using a measuring device (model number LFA-447) manufactured by Netsch Japan. The measurement temperature was 25°C. The thickness of the composite material in Example 1 was 2.731 mm, the thickness after polishing was 2.547 mm, and the thickness after pulse current sintering was 2.425 mm. The thickness of the composite material in Example 2 was 2.636 mm, and the thickness after polishing was 2.492 mm. The thickness of the heat dissipation substrate after pulse current sintering was 2.560 mm. The thickness of the composite material in Example 3 was 2.636 mm, and the thickness after polishing was 2.445 mm. The thickness of the heat dissipation substrate after pulse current sintering was 2.510 mm. The "relative density" before polishing, after polishing, and after re-pulse current sintering is shown in Table 2, the "thermal diffusivity" is shown in Table 3, and the "thermal conductivity" is shown in Table 4. The "relative density" in Table 2 indicates the relative ratio of the actual density to the true specific gravity of the composite material. In the case of Example 2 and Example 3, the true density after re-pulse current sintering is the density of the heat dissipation substrate in which the composite material and Cu powder particles or Cu plate are sintered, so the effect of re-pulse current sintering on the density becomes difficult to understand. Therefore, the transition of the relative density was obtained for each of "after composite material preparation", "after processing surface formation", and "after re-pulse current sintering".
[0080] [Table 2]
[0081] [Table 3]
[0082] [Table 4]
[0083] As can be seen from Tables 2 and 3, in all of the Examples, the relative density and thermal diffusivity decreased due to the polishing process. However, the relative densities of the heat dissipation substrates in Examples 1 to 3, which were subjected to re-pulse current sintering after forming the processed surface, were all higher than the relative density after the polishing process. Similarly, the thermal conductivity was also higher after re-pulse current sintering than after the polishing process.
[0084] In addition, in Examples 2 and 3, a metal layer with a thickness of about 0.2 mm exists on the surface. This metal layer is formed by performing pulse current sintering while contacting Cu powder particles or a Cu plate on the polished surface of the composite material, and is a Cu layer that does not contain diamond particles. On the other hand, in Example 1, diamond particles are also present in the surface region of the heat dissipation substrate. For this reason, in the heat dissipation substrates in Examples 2 and 3 in which the Cu layer is sintered as a single unit, as shown in Table 3, the thermal diffusivity after pulse current sintering does not seem to increase. However, considering the significant improvement in thermal conductivity in Example 1 and the presence of a Cu layer with a smaller thermal diffusivity than diamond in Examples 2 and 3, it can be concluded that the thermal diffusivity of the composite material 80 itself is increased by pulse current sintering in all Examples.
[0085] Next, an example of a process for preparing a composite material containing diamond and Cu will be described.
[0086] <Experimental Example 1> A mixed powder was obtained by mixing Cu powder particles with an average particle size of 5 μm and diamond particles with an average particle size of 250 μm. The total weight of the mixed powder was 6.24 grams. The Cu powder particles were 80 mass percent and the diamond particles were 20 mass percent of the total mixed powder. Next, a Cu-diamond MMC with a thickness of 3 mm was fabricated using a sintering device manufactured by SPS Syntex (model number SPS-515S). The sintering peak temperature Ts was 500°C, and the applied pressure was 36 MPa. The retention time at the sintering peak temperature Ts was 10 minutes. The degree of vacuum at the start of sintering was 10 Pa. The fabrication conditions and the estimated thermal conductivity are shown in Table 5.
[0087] <Experimental Examples 2 to 6> In Experimental Examples 2 to 6, as shown in Table 5 below, only the sintering temperature or both the sintering peak temperature Ts and the applied pressure were changed compared to Experimental Example 1 to obtain a Cu-diamond MMC. In Experimental Example 5, the diamond particles were used as a bimodal mixed powder. Diamond particles with an average particle size of 60 μm accounted for 10 mass percent of the entire Cu-diamond MMC, and diamond particles with an average particle size of 250 μm accounted for 20 mass percent.
[0088] <Experimental Example 7> A composite material was obtained in the same manner as in Experimental Example 1, except for the following points. The sintering temperature was 640°C, the first pressure was 10 MPa, and the second pressure was 36 MPa, which were repeatedly applied. The applied pressures were held for 15 seconds for the first pressure and 20 seconds for the second pressure, with a total pressure switching time of 50 seconds, for a total cycle time of 85 seconds. The number of repeated cycles was 25. The holding time of the sintering peak temperature Ts was 20 minutes.
[0089] <Experimental Examples 8 and 9> By varying the conditions as shown in Table 5, Cu-diamond MMCs were obtained.
[0090] In the process of preparing a composite material, a mixed powder of diamond particles and copper powder particles was prepared, and the mixed powder was subjected to pulse current sintering while being held at a temperature of 500°C or higher and lower than 800°C while being subjected to a pressure of 5 MPa or higher and 100 MPa or lower, to produce a composite material from the mixed powder. In Experimental Examples 1 to 9, the composite materials had a higher thermal conductivity than Cu alone. These composite materials in Experimental Examples 1 to 9 can be used as the composite materials in Examples 1 to 3 above.
[0091] [Table 5]
[0092] FIG. 13 is a diagram showing an optical microscope photograph of a cross section of a part of a composite material manufactured in the same manner as in Experimental Example 3 of Table 5. FIG. 14 is a diagram showing an optical microscope photograph of a cross section of a part of a composite material manufactured in the same manner as in Experimental Example 7 of Table 5. In each photograph, the relatively bright areas are Cu parts, and the relatively dark areas are diamond particles. In the composite material of FIG. 14, relatively small diamond particles with an average particle size of 60 μm are located in the gaps between relatively large diamond particles with an average particle size of 250 μm. Compared to the composite material of FIG. 13, the composite material of FIG. 14 has an increased number of diamond particles and an increased total surface area. This means that the interface area between Cu and diamond increases. If the interface area increases, the adhesion between diamond and Cu is poor, so that the thermal resistance increases and the thermal conductivity may decrease. However, such a phenomenon was not observed in this experimental example.
[0093] As can be seen from Figures 13 and 14, the composite material in the experimental example is dense.
[0094] <Application Examples> A configuration example of a light emitting device including a heat dissipation substrate manufactured according to an embodiment of the present disclosure will be described.
[0095] FIG. 15 is a perspective view showing a schematic configuration example of a light emitting device 200 including a light emitting diode (LED) 22 and a heat dissipation substrate 24 supporting the LED 22. The heat dissipation substrate 24 is manufactured by the manufacturing method in the above embodiment. An insulating layer 26, such as AlN, is formed on the upper surface of the heat dissipation substrate 24. A p-side wiring 28p and an n-side wiring 28n are formed on the insulating layer 26 and are electrically connected to the p-side electrode and the n-side electrode of the LED 22, respectively. The lower surface of the heat dissipation substrate 24 is in thermal contact with a heat sink or a cooling device (not shown). The heat generated by the LED 22 during operation is spread in the in-plane direction by the insulating layer 26, and then quickly dissipates to the outside via the heat dissipation substrate 24.
[0096] The configuration examples of the light emitting devices 200 and 300 described above are examples of semiconductor devices that utilize the composite material according to the embodiments of the present disclosure as a heat dissipation member, and this composite material can be used for various purposes. [Industrial Applicability]
[0097] The method for manufacturing a heat dissipation substrate according to the present disclosure provides a composite substrate that can be used as a variety of heat dissipation substrates. Examples of heat dissipation substrates include package bases, submounts, heat spreaders, packages, and heat sinks that are in thermal contact with elements such as semiconductor light emitting elements, semiconductor integrated circuit elements, and monolithic microwave integrated circuit elements. [Explanation of symbols]
[0098] 10···Diamond particles, 20···Cavity, 30···Die, 40···Upper punch, 50···Lower punch, 60···Power supply unit, 100···Sintering device
Claims
1. Providing a composite material comprising diamond and metal; a step of thinning a surface of the composite material to form a processed surface on the composite material; and heating the composite material by pulse current sintering while applying a pressure of less than 50 MPa to the composite material.
2. The method for manufacturing a heat dissipation substrate according to claim 1 , wherein the pulse current sintering is performed in a state where a metal powder or a metal plate is in contact with the processed surface of the composite material, thereby forming a metal layer bonded to the processed surface.
3. The method for manufacturing a heat dissipation substrate according to claim 2 , wherein the metal layer has a thickness of 50 μm or more and 500 μm or less.
4. The method for manufacturing a heat dissipation substrate according to claim 1 , wherein the pulse current sintering is performed without contacting a metal powder or a metal plate with the processed surface of the composite material.
5. The step of preparing the composite material includes: providing a powder mixture of diamond particles and copper powder particles; and generating the composite material from the mixed powder by pulse current sintering, the mixed powder being held at a temperature of 500° C. or more and less than 800° C. while applying a pressure of 5 MPa or more and 100 MPa or less to the mixed powder.
6. The method for producing a heat dissipation substrate according to claim 5 , wherein the amount of metal other than copper added to the mixed powder is 1% or less in terms of mass ratio.
7. The mass ratio of the copper powder particles in the mixed powder is 60% or more and 85% or less, The method for manufacturing a heat dissipation substrate according to claim 5 or 6, wherein a mass ratio of the diamond particles in the mixed powder is 15% or more and 40% or less.
8. The method for manufacturing a heat dissipation substrate according to claim 5 , wherein an average particle size of the diamond particles in the mixed powder is 200 μm or more and 400 μm or less.
9. The method for manufacturing a heat dissipation substrate according to claim 5 , wherein the diamond particles in the mixed powder include particles having an average particle size of 200 μm or more and 400 μm or less, and particles having an average particle size of 40 μm or more and 80 μm or less.
10. The method for producing a heat dissipation substrate according to claim 5 , wherein a pressure in the step of producing the composite material is 5 MPa or more and 50 MPa or less.
11. The method for manufacturing a heat dissipation substrate according to claim 10 , wherein the step of generating the composite material is performed by repeatedly applying a first pressure and a second pressure higher than the first pressure while maintaining the temperature.
12. The method for manufacturing a heat dissipation substrate according to claim 5 , wherein the copper powder particles have an average particle size of 3 μm or more and 10 μm or less.
13. Providing a composite material including diamond and metal that has been subjected to a thinning treatment; and heating the composite material by pulse current sintering while applying a pressure of less than 50 MPa to the composite material.
Citation Information
Patent Citations
Manufacture of polishing plate
JP2000225549A
Diamond particle-dispersed metal matrix composite material, and method for producing the same
JP2008248324A
HEAT SINK USING Cu-DIAMOND-BASED SOLID PHASE SINTERED BODY EXCELLENT IN HEAT RESISTANCE, DEVICE FOR ELECTRONICS USING THE HEAT SINK AND METHOD OF MANUFACTURING HEAT SINK USING Cu-DIAMOND-BASED SOLID PHASE SINTERED BODY EXCELLENT IN HEAT RESISTANCE
JP2014214363A
Heat sink material for high-power devices
JP2019502251A
Method of bonding a particle material to near theoretical density
US6001304A
